Aplikasi Laporan Berita Jurnalis Pada Surat Kabar Harian Sumut Pos Medan Menggunakan Kodular - Alda, Muhamad; Sweety, Miana; Rayhannur, M Jaffar; Toar, Miftahul Jannah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Various new print media have emerged in Indonesia with the same aim of providing complete information to the public. Current technology makes it easy for the journalism sector to use it as a means of conveying news information easily. Journalists as news content producers. Recording each member's journalistic activities is one of the journalist's duties in making news. Journalistic activity records are one of the main materials in consideration for making news. There are several stages of the waterfall model, namely: Requirements analysis, system design, coding, application testing, program implementation. The purpose of data analysis is to make it easier to design information in a system. There is some data used in creating an information system for journalists' daily reports in the North Sumatra Post daily newspaper, such as data analysis. This application can also make it easier for the North Sumatra Medan Post Office to monitor and manage journalists' news data. Equipped with a login application, security can be guaranteed from use by unauthorized people